Penerapan Hukum dalam Pembebanan Nafkah Istri Pasca Perceraian di Pengadilan Agama Limboto - Kartiningsi Dako (Al-Mizan (e-Journal), 2019)
This article discusses the livelihood of a post-divorce wife in the Limboto Religious Court by examining two decisions, namely Decision Number 419/Pdt.G/ 2016/PA.Lbt and Decision Number 618/Pdt.G/2018/PA.Lbt. These two decisions are different, although related to the burden of post-divorce wife's livelihood, so the problem in this article is how to apply the judge's law in determining the post-divorce wife's liability in the Limboto Religious Court? This research is a library research with a juridical normative approach. Data collected through literature study, then processed and analyzed descriptively qualitatively. The results showed the panel of judges of the Religious Court in the determination of the wife's post-divorce decision in the case of Decision Number 419/Pdt.G/2016/PA.Lbt and Decision Number 618/Pdt.G/2018/ PA.Lbt using the application of the law based on grammatical interpretation from the context of the husband's ability in terms of income, namely the actual ability and potential ability.